Capital-Labor Substitution Among States: Some Empirical Evidence - Marcus, Matityahu (The Review of Economics and Statistics, 1964)
In this article we study the variations in capitallabor ratios among states for manufacturing industries and the role of price-induced substitution as a factor influencing the observed variations. In the first part, differences in output composition within industries are ignored. In the second part, these differences are considered and we are able to suggest whether the observed substitution is achieved through an appropriate selection of output mix, or through pure substitution, that is, substitution of factors given the same output mix.